Nanomateriais híbridos contendo prata e óxido de grafeno reduzido para atividade antifúngica - Almeida, Bianca Gottardo [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
Superficial infections of hair, skin or nails, mainly caused by fungi, are often reported by patients in dermatology clinics. In addition to the esthetic impact, itching, pain, nail and tissue deformity, can be a source of entry for other opportunistic or primary pathogens, covering more itchy tissues. The high cost of treatment, toxicity and emergence of resistant pathogens justify the search for new drugs. The aim of this study was to evaluate the antimicrobial activity of reduced graphene oxide (rGO/Ag) and silver nanocomposites (NCs) against microrganisms clinically isolated belonging to the Microbiology Laboratory of the Faculty of Medicine of São José do Rio Preto - FAMERP. The NCs were characterized by X-ray diffraction analysis, and the morphology and characterization of the nanocomposite were investigated by transmission electron microscopy. The antifungal susceptibility assay was performed by the microdilution method based on the CLSI protocol, with modifications. The toxicological profile was tested in vivo model. The hybrid nanoparticles showed great inhibitory effect against all clinical tested strains, without toxicity. In summary this study provides a new alternative therapeutic strategy for the control of dermatomycoses.

As infecções superficiais de cabelo, pele ou unhas, frequentemente causadas por fungos, são reportadas por pacientes em clínicas dermatológicas. Além do impacto estético, dor, prurido, deformidade ungueal e tecidual, podem ser fonte de entrada para outros patógenos primários ou oportunistas alcançando tecidos mais profundos. O alto custo do tratamento, a toxicidade e surgimento de patógenos resistentes justificam a busca por novas drogas. Sendo assim, o objetivo deste estudo foi avaliar a atividade antifúngica de nanocompósitos (NCs) de óxido de grafeno reduzido e prata (rGO/Ag) contra isolados clínicos de microrganismos pertencentes ao laboratório de Microbiologia da Faculdade de Medicina de São José de São José do Rio Preto. As NCs foram caracterizadas por análise de difração de raios X, e a morfologia e caracterização do nanocompósito, foram investigadas por microscopia eletrônica de transmissão. O ensaio de suscetibilidade antifúngica foi realizado pelo método de microdiluição seguindo o protocolo CLSI, com modificações. O perfil toxicológico foi testado em modelo in vivo. As nanopartículas híbridas apresentaram grande potencial inibitório frente as cepas clínicas, sem toxicidade. Este estudo fornece nova estratégia terapêutica alternativa para o controle de dermatomicoses.
Hybrid nanomaterials with reduced graphene oxide and silver against fungi species
Keywords: Dermatomycoses; Reduced graphene oxide; Silver nanoparticles; Antifungal; Dermatomicoses; Óxido de grafeno reduzido; Nanopartículas de prata; Antifúngicos